A Glucosinolate Mutant of Arabidopsis Is Thermosensitive and Defective in Cytosolic Hsp90 Expression after Heat Stress - Ludwig-Müller, Jutta (American Society of Plant Physiologists, 2000)
The TU8 mutant of Arabidopsis previously described to be deficient in glucosinolate metabolism and pathogen-induced auxin accumulation was found to be remarkably less tolerant upon exposure to elevated temperatures than wild-type plants. Although moderately increased temperature only affected shoot growth, exposure to severe heat stress led to a dramatic decay of mutant plants. By contrast, wild-type seedlings showed little or no damage under the same conditions. Analysis of different heat stress proteins (Hsps) in TU8 seedlings revealed that only expression of cytoplasmic Hsp90 was affected in these plants. Although Hsp90 was present under control conditions, its level declined in mutant plants at elevated temperatures. Northern-blot analysis indicated that the decrease in Hsp90 protein was accompanied with a reduction of hsp90 transcript levels. Transient expression of Hsp90 in mutant protoplasts increased their survival rate at higher temperatures to near equivalent that of wild-type protoplasts. These data suggest that the reduced level of Hsp90 in TU8 mutants may be the primary cause for the observed reduction in thermostability.